Afro-Amazonian Sankofa Women.: Educational Processes in Political Movement. (Interdisciplinary Studies Journal, 2024)
In the territory of rivers, streets, and roads of the municipality of Abaetetuba, Afro-Amazonian women in rhizomes of knowledge weave support networks, political strengthening, organized social struggle, and exchanges. It is in this place that the Black Women’s Collective Sankofa promotes anti-racist and political education in the Lower Tocantins. The objective of this research is to analyze the formation, participation, and knowledge created and disseminated by the Sankofa Black Collective. The Cartography of Rhizomes, based on Deleuze and Guattari (1995), was the methodology chosen for this study, due to the networks of multiplicity, freedom for research, and decentralization of knowledge that cartography enables. Supported by: BERTH (2019); COLLINS (2019); DAVIS (2016, 2017); DELEUZE and GUATTARI (1995); GOMES (2017, 2019), KILOMBA (2019); PRIOLI (2022). Sankofa is repeatedly requested to give lectures and debates in both formal and informal teaching spaces. This suggests that it is a movement that educates the educational and political field, with implications for the municipality of Abaetetuba, Igarapé-Miri, and surrounding areas. The capacity to produce emancipatory educational practices, political constructions, and the positivity of Black aesthetics and quilombado encounters is evident, and these constructions resulted in the achievement of an anti-racist mandate.
Keywords: Antiracist Education; Black Women; Black Movement; Politics